2022
DOI: 10.1002/cta.3512
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on transmission performance of multi‐stage wireless power transfer systems using SPS compensation and LCC compensation

Abstract: The new multi-stage wireless power transfer (WPT) systems based on seriesparallel-series (SPS) and inductor-capacitor-capacitor (LCC) compensations (SPS-WPT and LCC-WPT) are characterized by constant output current and high transmission efficiency. To obtain applicable conditions and performance differences of these two systems, their output characteristics have been studied by theoretical derivation and experimental verification. First, the equivalent models of double-stage SPS-WPT and LCC-WPT systems have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The mutual inductance ( M) is calculated as M=kL1L2. The equivalent load resistance ( RLtrue) of the full bridge rectifier is defined as [26, 27] RLgoodbreak=8ROπ2. …”
Section: Analysis Of the Series–series‐compensated Wpt Systemmentioning
confidence: 99%
“…The mutual inductance ( M) is calculated as M=kL1L2. The equivalent load resistance ( RLtrue) of the full bridge rectifier is defined as [26, 27] RLgoodbreak=8ROπ2. …”
Section: Analysis Of the Series–series‐compensated Wpt Systemmentioning
confidence: 99%
“…14 However, it is reported that the power transfer efficiency of the WPT system will drop dramatically when the charging distance increases. 15 To improve transfer efficiency, several methods including changing coil structure, [16][17][18] designing impedance matching circuits, 19 and adding nonlinear elements have been proposed. 20 In addition to the above approaches, metamaterial (MTM) also offers an alternative to cope with the problem that transfer efficiency is low at long charging distances.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that the power transfer efficiency of the WPT system will drop dramatically when the charging distance increases 15 . To improve transfer efficiency, several methods including changing coil structure, 16–18 designing impedance matching circuits, 19 and adding nonlinear elements have been proposed 20 …”
Section: Introductionmentioning
confidence: 99%
“…To reduce the size and cost of an additional inductor, compensation capacitors are usually used in series with the transmitter coil to form an LCC compensation network. 30,31 An LCC compensation network is used to achieve zero phase angle (ZPA) with constant voltage output by adjusting the compensation network parameters. 32,33 In traditional WPT system, a stable DC power supply is typically used as the input voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The LCL topology has the following two advantages: The inverter only provides active power at the secondary side; the current of the transmitting coil is independent of the load value. To reduce the size and cost of an additional inductor, compensation capacitors are usually used in series with the transmitter coil to form an LCC compensation network 30,31 . An LCC compensation network is used to achieve zero phase angle (ZPA) with constant voltage output by adjusting the compensation network parameters 32,33 …”
Section: Introductionmentioning
confidence: 99%